Awakening efficacy of a vibrotactile device in patients on home nocturnal ventilatory assistance and healthy subjects as family caregiver proxies. (28th December 2020) - Attali, Valerie; Lavault, Sophie; Guerder, Antoine; Al-Youssef, Saba; Dudoignon, Benjamin; Taytard, Jessica; Arnulf, Isabelle; Faure, Morgane; Straus, Christian; Similowski, Thomas; ,
The objective of this study was to test the capacity of vibrotactile stimulation transmitted to the wrist bones by a vibrating wristband to awaken healthy individuals and patients requiring home mechanical ventilation during sleep. Healthy subjects (n = 20) and patients with central hypoventilation (CH) (Congenital Central Hypoventilation syndrome n = 7; non-genetic form of CH n = 1) or chronic obstructive pulmonary disease (COPD) (n = 9), underwent a full-night polysomnography while wearing the wristband. Vibrotactile alarms were triggered five times during the night at random intervals. Electroencephalographic (EEG), clinical (trunk lift) and cognitive (record the time on a sheet of paper) arousals were recorded. Cognitive arousals were observed for 94% of the alarms in the healthy group and for 66% and 63% of subjects in the CH and COPD groups, respectively (p < 0.01). The percentage of participants experiencing cognitive arousals for all alarms, was 72% for healthy subjects, 37.5% for CH patients and 33% for COPD patients (ns) (94%, 50% and 44% for clinical arousals (p < 0.01) and 100%, 63% and 44% for EEG arousals (p < 0.01)). Device acceptance was good in the majority of cases, with the exception of one CH patient and eight healthy participants. In summary this study shows that a vibrotactile stimulus is effective to induce awakenings in healthy subjects, but is less effective in patients, supporting the notion that a vibrotactile stimulus could be an effective backup to a home mechanical ventilator audio alarm for healthy family caregivers.